2016
DOI: 10.1097/j.pain.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

The effect of local vs remote experimental pain on motor learning and sensorimotor integration using a complex typing task

Abstract: Recent work demonstrated that capsaicin-induced acute pain improved motor learning performance; however, baseline accuracy was very high, making it impossible to discern the impact of acute pain on motor learning and retention. In addition, the effects of the spatial location of capsaicin application were not explored. Two experiments were conducted to determine the interactive effects of acute pain vs control (experiment 1) and local vs remote acute pain (experiment 2) on motor learning and sensorimotor proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
75
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(92 citation statements)
references
References 69 publications
16
75
1
Order By: Relevance
“…Typically, motor deficits are regarded as a consequence of movement-related pain; however, there is evidence that pain affects motor control and has the ability to negatively influence the neuroplasticity associated with motor output (Bank et al 2013;Hodges and Tucker 2011;Mercier and Leonard 2011). While the presence of acute pain during motor learning may interfere with skill acquisition (Boudreau et al 2007;Flor 2003;Schweinhardt et al 2006), our recent studies (Dancey et al 2014(Dancey et al , 2016 demonstrated that motor learning acquisition improved in the presence of acute pain. A limitation of previous work (Andrew et al 2015;Dancey et al 2014Dancey et al , 2016 is that learning saturation occurred with these typing tasks as baseline accuracy was high.…”
Section: New and Noteworthymentioning
confidence: 67%
See 3 more Smart Citations
“…Typically, motor deficits are regarded as a consequence of movement-related pain; however, there is evidence that pain affects motor control and has the ability to negatively influence the neuroplasticity associated with motor output (Bank et al 2013;Hodges and Tucker 2011;Mercier and Leonard 2011). While the presence of acute pain during motor learning may interfere with skill acquisition (Boudreau et al 2007;Flor 2003;Schweinhardt et al 2006), our recent studies (Dancey et al 2014(Dancey et al , 2016 demonstrated that motor learning acquisition improved in the presence of acute pain. A limitation of previous work (Andrew et al 2015;Dancey et al 2014Dancey et al , 2016 is that learning saturation occurred with these typing tasks as baseline accuracy was high.…”
Section: New and Noteworthymentioning
confidence: 67%
“…While the presence of acute pain during motor learning may interfere with skill acquisition (Boudreau et al 2007;Flor 2003;Schweinhardt et al 2006), our recent studies (Dancey et al 2014(Dancey et al , 2016 demonstrated that motor learning acquisition improved in the presence of acute pain. A limitation of previous work (Andrew et al 2015;Dancey et al 2014Dancey et al , 2016 is that learning saturation occurred with these typing tasks as baseline accuracy was high. If the learning task difficulty is not high enough, differences between groups may not be observed and a type II error may be likely (Dancey et al 2014(Dancey et al , 2016.…”
Section: New and Noteworthymentioning
confidence: 67%
See 2 more Smart Citations
“…It would be of interest in further studies to assess both pain-induced modulation in S1 excitability and SAI given the results of recent studies showing that a decrease in S1 excitability induced by non-invasive stimulation results in a reduction of the amount of SAI. At this stage, the impact of nociceptive stimuli on S1 excitability (as measured by the short latency components of somatosensory evoked potentials) remains unclear, especially for cutaneous nociceptive modalities [30,31,40,41,42,43,44,45]. One also needs to consider that the nociceptive modality and the location of the nociceptive stimuli with respect to the tested muscle might influence the results.…”
Section: Discussionmentioning
confidence: 99%